Investigating the limitations of the discharge-head relationship of compound crump weirs exceeding their hydraulic capacities - Van Vuuren, S.J. (University of Pretoria, 2021)
Dissertation (MEng (Water Resources Engineering))--University of Pretoria, 2020.